The characteristics of shallow geological structure for Red River side - Tay Ho - Hanoi area by geophysical data - Giang, Nguyen Van; Hida, Noboru; Bano, Maksim (Vietnam Journal of Earth Sciences, 2012)
The study of shallow geological structure by geophysical data is interested for many scientists by advanced geophysical technology nowadays. The exploiting groundwater is too much by time for domestic and social-economic development.The complex of geophysical methods as well as electrical sounding and profiling and electromagnetic methods such as Georadar and VLF were carried out by longitudinal and cross-lines in the study area for near-surface structure investigation. The measured geophysical data were processed and interpreted by modern geophysical tools. The results are clearly shown anisotropy and  inhomongeneous of shallow structure by morphology for the study area. The near-surface structure consists of  5 layers upto 30 m of depth revealed by GPR data. The depths of the second and third layers in different locations are alternately corresponding to the river-bed levels. This is a good condition for linked assessment between aquifers and possibility for recharge by the Red River water to groundwater on right side of the river.